PENGARUH LIKUIDITAS, PROFITABILITAS DAN LEVERAGE TERHADAP FINANCIAL DISTRESS DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2024 - Tasya Mega; Aulia, Tasya Mega; Gumilarsih, Basis; Nelyumna (Relevan : Jurnal Riset Akuntansi, 2025)
This study aims to analyze the effect of liquidity, profitability, and leverage on financial distress, as well as the role of managerial ownership as a moderating variable in this relationship. This study employs a quantitative approach with a causal-comparative design. The population consists of manufacturing companies in the basic industry and chemical sectors listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. The sample was selected using purposive sampling, with a sample size of 32 companies. Data were analyzed using panel data regression with the assistance of EViews 12 software. The results indicate that liquidity and profitability have a positive effect on financial distress, while leverage has a negative effect on financial distress. Additionally, managerial ownership was found to moderate the relationship by weakening the effect of liquidity on financial distress, but it did not moderate the relationship between profitability and leverage on financial distress.